Stochastic assessment of bond-slip behavior of plain round bars in low strength concrete - Yurdakul, Özgür; Balaban, Eren; Artagan, Salih Serkan; Řoutil, Ladislav (Elsevier Science, 2021)
The effect of inherent uncertainties in material properties on the global response of beam-type bond-slip specimens constructed from the low strength concrete and plain round bar was investigated by the stochastic study. First, the substandard specimens were tested up to failure under monotonic loading. Bond-slip models, which were derived from the experimental data, were proposed for confined and unconfined RC members with poor concrete quality and plain round bars. Then, the proposed bond-slip relations were implemented in numerical models. The experimentally validated finite element (FE) models were combined with a suitable stochastic sampling technique (Latin Hypercube Sampling (LHS)). Therefore, the variability in the identical tests was characterized by stochastic computational mechanics. The load-displacement curves in the stochastic analysis formed a band around the deterministic model which also simulated the dispersion in the experimental capacity. Besides, the randomized behavior provided the basic statistical parameters of the response quantity. Finally, the partial correlation coefficient between input variables (i.e., material parameters) and response variable was evaluated to outline the material parameters which mainly govern the global response (i.e., sensitivity analysis). It is found that the relative impact of the concrete tensile strength on the ultimate capacity was the most significant.
Keywords: bond-slip; plain round bar; substandard; low strength concrete; sensitivity; stochastic assessment; finite element